The Effect of Functional Interpersonal Communication Skills of Tax Exten-sion Officers on Improving Tax Reporting Compliance at the South Makassar Tax Service Office - Maswar, Muhammad Azwar; Unde, Alimuddin; Arianto, Arianto (IHSA Institute, 2025)
This study aims to analyze and understand the level of functional interpersonal communication skills of tax extension workers, the level of taxpayer compliance, taxpayer awareness and the magnitude of the influence of the level of functional interpersonal communication skills of tax extension workers on the improvement of tax reporting compliance at the South Makassar Pratama Tax Service Office. This study uses a quantitative method using an interpersonal communication skills approach and data collection is carried out through the distribution of questionnaires. The variables tested were the influence of functional interpersonal communication skills of tax extension workers, understanding and awareness of taxpayers on increasing taxpayer compliance. The results of the study show that the level of functional interpersonal communication skills of tax extension workers, the level of understanding and the level of tax awareness simultaneously have a positive and significant effect on tax reporting compliance. This is marked by a calculated F value (21,712) greater than the F table (2.68) and a significance value of 0.000 less than 0.05 as the threshold of the set significance value. However, when tested partially, only one variable had a positive and significant effect on the improvement of tax compliance, namely the level of functional interpersonal communication skills of tax extension workers. Meanwhile, the variables of the level of understanding and awareness of taxpayers have a negative effect